Effect of a unilateral hind limb orthotic lift on upper body movement symmetry in the trotting horse. - Jodi Vertz; Diana Deblanc; Marie Rhodin; Thilo Pfau (PLoS ONE)
In trotting horses, movement asymmetry is associated with ground reaction force asymmetry. In humans, limb length differences influence contralateral force production. Here we investigate whether horses, in immediate reaction to limb length changes, show movement asymmetry adaptations consistent with reported force differences. Aim of this study was to quantify pelvic and compensatory head and withers movement asymmetry as a function of limb length changes after application of orthotic lifts. In this experimental study movement asymmetry of eleven trotting horses was calculated from vertical displacement of poll, withers, sacrum and left and right tuber coxae with inertial sensors. Horses were assessed in-hand under 5 conditions (all with hind limb boots): without orthotic lifts, and with a 15mm or 30mm orthotic lift applied to the left hind or right hind. A linear mixed model investigated the influence of orthotic lift condition (P<0.05, pairwise posthoc Bonferroni correction). Pelvic movement asymmetry showed increased pelvic downward movement during stance of the shorter limb and increased pelvic upward movement during and after stance of the longer limb (P<0.001) with asymmetry changes of 3-7mm (4-10mm) for 15mm (30mm) lifts. Hip hike (tuber coxae movement asymmetry) was unaffected (P = 0.348). Head and withers movement asymmetry were affected less consistently (2 of 3 respectively 1 of 3 head or withers parameters). The small sample size of the study reduced generalizability, no direct force measurements were conducted and only immediate effects of orthotic lifts were assessed with no re-assessments days or weeks after. Conclusions about mechanical consequences (weight bearing, pushoff) are based on published movement-force associations. Pelvic movement asymmetry with an artificial change in limb length through application of an orthotic lift indicates increased weight support with the shorter limb and increased pushoff with the longer limb. This may be of relevance for the management of horses with different hoof shapes between contralateral limbs, for example some chronically lame horse.